Influence of nominal distortion of Beidou-3 B1C signal on ranging performance - Xue WANG; Yao GUO; Yongnan RAO; Xiaochun LU; Li KANG (Tongxin xuebao)
The B1C signal is selected as a civil navigation signal for the BDS-3 system,which adopts a complex constant envelope modulation in the B1 frequency band.Therefore,it is easy to generate nominal distortion during signal generation.Such nominal distortion of each satellite produces inconsistent ranging deviation and directly degrades the system positioning performance.A complete ranging deviation estimation method was proposed for B1C signals in this paper.Firstly,the S-Curve Bias (SCB) was used to quantitatively analyze the B1C signal ranging deviation,and the standard correlation curve estimation method was proposed to realize the accurate estimation of the code phase deviation at the peak of the correlation curve.Secondly,a algorithm was designed to solve the problem of QMBOC signal mislocking at the platform during receiver tracking.Finally,the actual ranging bias and nature ranging bias of each satellite of Beidou-3 under different correlation intervals and front-end bandwidth of the user receiver were analyzed based on the satellite downlink signals collected from the 40-meter high-gain antenna at the National Time Service Center,and the recommended user receiver parameter range was given.The strategy proposed in this paper can be extended to other MBOC signal ranging error estimation,and the test results can be thought of as a reference to the development of BeiDou-3 receiver.